FLC: A novel dynamic buffer tuner for shortening service roundtrip time over the Internet by eliminating user-level buffer overflow on the fly - Lin, W.; Wong, A.; Dillon, Tharam S. (Springer, 2005)
The proposed Fuzzy Logic Controller (FLC) is for dynamic buffer tuning at the user/server level. It eliminates buffer overflow on-line by ensuring that the buffer length always cover the queue length adaptively. The FLC contributes to prevent the AQM (active queue management) resources dished out at the system level from being wasted and to shorten the service roundtrip time (RTT) by reducing retransmission caused by user-level buffer overflow at the reception side. Combining fuzzy logic and the conventional PIDC model creates the FLC that operates with the {0,?}2 objective function. The fuzzy logic maintains the given safety margin about the reference point, which is symbolically represented by “0” in {0,?}2 . The short execution time of the FLC makes it suitable for supporting time-critical applications over the Internet.